УБАВИНАТА НА МАКЕДОНИЈА ВО СВЕСТА НА МАКЕДОНЦИТЕ - ПО ПРИМЕРИ НА НАРОДНАТА ТРАДИЦИЈА (Filološke pripombe, 2019)
The natural beauties with which Macedonia as a country is embellished are irresistible. It is what influences people’s conscience in many ways. In the nature of human soul and man’s existence, the basic need for beauty is deep-seated as well as the need for creations with which beauty is noblefied. Thus, Macedonian folk genius couldn’t encircle this basic need and so he incorporated it in his work. It is without doubt an indication of the unrestricted possibilities of the Macedonian word. Love your country, love all the beauties that nature gave you and which Macedonian man has created throughout the centuries. It is a simple and noble message. We are com- pelled to honor and cherish it.